Late Holocene environmental conditions in Coronation Gulf, southwestern Canadian Arctic Archipelago: evidence from dinoflagellate cysts, other non-pollen palynomorphs, and pollen - Pieńkowski, A. J.; Mudie, Peta J.; England, John H.; Smith, John N.; Furze, Mark F. A. (Journal of Quaternary Science, 2011)
Boxcore 99LSSL-001 (68.095°?N, 114.186° W; 211?m water depth) from Coronation Gulf represents the first decadal-scale marine palynology and late Holocene sediment record for the southwestern part of the Northwest Passage. The record was studied for organic-walled microfossils (dinoflagellate cysts, non-pollen palynomorphs), pollen, terrestrial spores, and sediment characteristics. 210Pb, 137Cs, and three accelerator mass spectrometry 14C dates constrain the chronology. Three prominent palaeoenvironmental zones were identified. During the interval AD 1470?1680 (Zone I), the climate was warmer and wetter than at present, and environmental conditions were more favourable to biological activity and northward boreal forest migration, with reduced sea-ice and a longer open-water (growing) season. The interval AD 1680?1940 (Zone II) records sea-ice increase, and generally cool, polar conditions during the Little Ice Age. During AD 1940?2000 (Zone III), organic microfossils indicate an extended open-water season and decreased sea-ice, with suggested amelioration surpassing that of Zone I. Although more marine studies are needed to place this record into an appropriate context, the succession from ameliorated (Zone I) to cooler, sea-ice influenced conditions (Zone II) and finally to 20th-century warming (Zone III) corresponds well with several terrestrial climatic records from the neighbouring mainland and Victoria Island, and with lower-resolution marine records to the west. Copyright © 2011 John Wiley & Sons, Ltd.
id: 2344